CAN A PROPER STRATEGIC PLANNING SECURE ITS IMPLEMENTATION? A CASE IN NEW DISTRICT IN DEVELOPING COUNTRY - Firda Hidayati (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
Strategic planning is highly recommended  as one of the key  factors that  determine the success  of the organization. However, only a few organizations  succeed in  implemented it. The research studied  causes of poor  strategy implementation. The study used  Data collection techniques included previous research on factors that influence   strategy implementation failures, and a survey of . three levels of managers in  38 agencies in the government. Using structural Equation Modelling-Partial Least Squares (SEM-PLS) as an analysis tool, results showed that   stakeholder uncertainty, resources, and expertise are the major factors that influence the failure of strategy  implementation.  The finding provides an  important  explanation for poor  strategy implementation performance in Batu Bara , which is a new district in Indonesia.  One of the key policy recommendations is for the government to take measures toward  enhancing  the capacity of managers to manage stakeholders’ uncertainty.